The Effect of Self-Disclosure on Loneliness in Adolescents During COVID-19: The Mediating Role of Peer Relationships - Chen, Li; Cheng, Rui; Hu, Bo (Frontiers in Psychiatry, 2021)
Long-term home isolation has had a certain impact on adolescents' enthusiasm for interpersonal communication and desire for self-disclosure during COVID-19. The purpose of this study was to explore the relationship between adolescents' self-disclosure and loneliness during COVID-19, and to analyze the mediating role of peer relationship in it. We conducted a cross-sectional study involving 830 Chinese adolescents (males: 47.5%, Mage14.25 years; females: 52.05%, Mage 14.19 years; Age range 12-15). Participants completed a self-reported survey that included sociodemographic, Jourard Self-Disclosure Scale, UCLA, and Peer Relationship Scale. The results showed that in the period of COVID-19, adolescents' self-disclosure affects loneliness through peer relationship, that is, the level of self-disclosure can significantly predict loneliness through peer relationship, and peer relationship plays a complete mediating role.